Single molecule identification of homology-dependent interactions between long ssRNA and dsDNA - Liu, Chenli (Nucleic Acids Res, 2017)
Long non-coding RNAs (lncRNAs) are prominently associated with chromosomes in an ever-increasing diversity of roles. To provide further insight into the potential nature of these associations, we have explored, for the first time, the interaction of long single-stranded (ss) RNAs with cognate homologous double-stranded (ds) DNA in vitro. Using magnetic tweezers, we measured the effects of ssRNA on force extension curves for dsDNA. We observe that the presence of ssRNA impedes the extension of dsDNA, specifically at low forces, dependent on homology between the RNA and DNA species, and dependent on ssRNA lengths (≥1 kb). The observed effect also depends on the concentration of ssRNA and is abolished by overstretching of the dsDNA. These findings show that significant homologous contacts can occur between long ssRNA and dsDNA in the absence of protein and that these contacts alter the mechanical properties of the dsDNA. We propose that long ssRNA interacts paranemically with long dsDNA via periodic short homologous interactions, e.g. mediated by RNA/DNA triplex-formation, and that dsDNA extension is impeded by formation of RNA secondary structure in the intervening unbound regions. Analogous interactions in vivo would permit lncRNAs to mediate the juxtaposition of two or more DNA regions on the same or different chromosomes.